1999
DOI: 10.1080/03079459994605
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic Escherichia coli in Psittaciformes

Abstract: A total of 103 Escherichia coli isolates from psittaciform birds were examined for the presence of genes coding for shigatoxin 1 (Stx1), shigatoxin 2 (Stx2) and for intimin (eae), using the polymerase chain reaction (PCR). Sixty-eight E. coli strains were isolated from necropsy cases and faecal samples, the other 35 were from 205 cloacal swabs from Psittaciformes with various conditions. All isolates were tested for enterohaemorrhagic E. coli-haemolysin (HlyEHEC), some also for Stx production, but there was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
1
16
2
4
Order By: Relevance
“…Health surveillance surveys focusing on this species help surviving captive curassows by enhancing husbandry practices, which consequently improve population numbers and stability. Although some studies have been published involving pathogenic Escherichia coli detection in other species of birds, mainly Psittaciformes and Columbiformes (Schremmer et al 1999, Pedersen et al 2006, Gonçalvez et al 2010, Knobl et al 2011, Saindenberg et al 2012), is still difficult to interpret the positive results found in asymptomatic curassows.…”
Section: Discussionmentioning
confidence: 81%
“…Health surveillance surveys focusing on this species help surviving captive curassows by enhancing husbandry practices, which consequently improve population numbers and stability. Although some studies have been published involving pathogenic Escherichia coli detection in other species of birds, mainly Psittaciformes and Columbiformes (Schremmer et al 1999, Pedersen et al 2006, Gonçalvez et al 2010, Knobl et al 2011, Saindenberg et al 2012), is still difficult to interpret the positive results found in asymptomatic curassows.…”
Section: Discussionmentioning
confidence: 81%
“…The isolates were found especially in aquatic birds and in a lesser degree among Passeriformes and Piciformes (Oh et al 2011). In a study involving psittacines, four isolated samples were characterized as typical EPEC and thre e as atypical isolates, all of which originated from clinical cases of diarrhea, enteritis, or septicemia, and suggested that these E. coli could have implications for human health (Schremmer et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies among wild birds have determined the classiϐication of pathog enic E. coli strains (Foster et al 1998, Steele et al 2005, and those involving psittacines found a degree of correspondence between disease and certain pathotypes (Schremmer et al 1999, Knöbl et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…None of the isolates analyzed here possessed the genes that encoded toxins LT, STa, STb, Stx1, Stx2, Hly or CNF. Schremmer et al (1999) examined E. coli isolated from psittaciformes and emphasized the presence of seven strains belonged serovars O63:H10, O110:H6, O131:H-, O153:H10 and ONT:H6, that were positive for the eae gene, four of which were also positive for the bfpA gene. The authors concluded that EPEC should be considered as potential pathogens in psittaciform birds, and may be a reservoir of human EPEC infections.…”
Section: Discussionmentioning
confidence: 99%
“…The potentially pathogenic E. coli strains can be screened by different tests, like phenotypic assays as Congo red binding (Styles & Flammer 1991), serotyping (Schremmer et al 1999), and genotypic assays (Pakpinyo et al 2002, Knöbl et al 2008, Nakazato et al 2009). …”
Section: Discussionmentioning
confidence: 99%